Reindeer lichen productivity: Problems and possibilities - Sveinbjörnsson, Bjartmar (Rangifer, 1990)
Reindeer lichens are important in the structure and function of tundra and taiga ecosystems, as exemplified by cover values, biomass, mineral content, and effect on other ecosystem components. They are particularly important for winter ecology of reindeer and caribou which largely relay on them. Growth measurement is difficult due to the very slow rate and the methods that have been used are not sufficiently documented, precise, or appropriate. Use of carbon dioxide exchange models, coupled with models of lichen microclimate and water relations, based on microclimatic data are suggested as alternatives for land managers. The assumptions of such models are discussed and the performance of mixed species lichen mats and of the lichen CO2 environment and its effect on lichen CO2 exchange.